2014
DOI: 10.3390/molecules190811560
|View full text |Cite
|
Sign up to set email alerts
|

Active Components with Inhibitory Activities on IFN-γ/STAT1 and IL-6/STAT3 Signaling Pathways from Caulis Trachelospermi

Abstract: Abstract:Initial investigation for new active herbal extract with inhibiting activity on JAK/STAT signaling pathway revealed that the extract of Caulis Trachelospermi, which was separated by 80% alcohol extraction and subsequent HP-20 macroporous resin column chromatography, was founded to strongly inhibit IFN-γ-induced STAT1-responsive luciferase activity (IFN-γ/STAT1) with IC 50 value of 2.43 μg/mL as well as inhibiting IL-6-induced STAT3-responsive luciferase activity (IL-6/STAT3) with IC 50 value of 1.38 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(29 reference statements)
3
12
0
Order By: Relevance
“…ARC inhibited autophagy as well as apoptosis by suppressing IFN-γ/IL-6/Stat1 signaling and IL6/Bnip3 signaling. The previous study of luciferase activity test showed that ARC could inhibit the IFN-γ/Stat1 and IL-6/Stat3 signaling ( 122 ), while present study demonstrated the inhibitions of both IFN-γ/IL-6/Stat1 signaling and IL6/Bnip3 signaling contributed to the protective effects of ARC against ConA-induced hepatitis.…”
Section: Discussionsupporting
confidence: 53%
“…ARC inhibited autophagy as well as apoptosis by suppressing IFN-γ/IL-6/Stat1 signaling and IL6/Bnip3 signaling. The previous study of luciferase activity test showed that ARC could inhibit the IFN-γ/Stat1 and IL-6/Stat3 signaling ( 122 ), while present study demonstrated the inhibitions of both IFN-γ/IL-6/Stat1 signaling and IL6/Bnip3 signaling contributed to the protective effects of ARC against ConA-induced hepatitis.…”
Section: Discussionsupporting
confidence: 53%
“…And it has been reported to mediate various cellular functions, including gene activation, cell differentiation, cell survival, and proliferation [18][19][20]. Notably, a number of growth factors and cytokines such as TGF-b1 [21], IFN-c [22], and IL-6 [23][24][25], oncostatin M (OSM) [26], high glucose (HG) [27], and Ang II [28] have been found to trigger this pathway, and then induce expression of multiple genes, including profibrotic [29] and pro-inflammatory genes [30]. Evidence derived from numerous clinical and animal models studies is emerging for the involvement of JAK/STAT cascade in renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…The compound luteolin 4′- O -glucuronide [ 8 ] (7.3 mg) was obtained directly from the fraction 22. Fraction 6 was chromatographed using RP18 HPLC with MeOH/H 2 O (42:58, v/v) as mobile phase (flow rate 2.0 mL min −1 ) to yield pure compound nortrachelogenin 4,4′-di- O -ß-D-glucopyranoside ( 2 ) [ 9 ] (1.1 mg, t R 36 min). Fraction 8 was isolated using RP18 HPLC with MeOH/H 2 O (37:63, v/v) as mobile phase (flow rate 2.0 mL min −1 ) to yield pure compounds chlorogenic acid [ 10 ] (8.1 mg, t R 8 min), neochlorogenic acid [ 11 ] (3.0 mg, t R 9 min), naringenin-7- O -neohesperidoside [ 12 ] (19.2 mg, t R 27 min), quercetin-3- O - α -L-rhamnopyranosyl-(1→6)- β -D-glucopyranoside [ 13 ] (3.0 mg, t R 52 min), apigenin-7- O - α -L-rhamnopyranosyl-(1→6)- β -D-glucopyranoside [ 14 ] (1.4 mg, t R 62 min), and Kaempferol-3- O - α -L-rhamnopyranosyl-(1→6)- β -D-glucopyranoside [ 13 ] (1.9 mg, t R 82 min).…”
Section: Methodsmentioning
confidence: 99%